Tildrakizumab for Moderate-to-Severe Plaque Psoriasis: An Evidence-Based Review (Canadian Dermatology Today, 2021)
Tildrakizumab is a fully human monoclonal antibody that selectively targets the p19 subunit of interleukin-23 (IL-23). It has been approved for the treatment of adults with moderate-to-severe plaque psoriasis in several countries. The standard dose is 100 mg by subcutaneous injection at weeks 0 and 4, then every 12 weeks thereafter, although a 200 mg dosage at the same interval does have approval in some jurisdictions.The aim of this article is to review the available evidence for tildrakizumab in treating moderate-to-severe chronic plaque psoriasis. In-depth discussion will be limited to pivotal studies and post hoc analyses.